The Problematic of Home in Exile - Chishti, Farida (Journal of Research in Humanities, 2023)
In the contemporary world of cross-cultural intermingling, this paper addresses the problematic of native home in diaspora in the fiction of Gao Xingjian. Gao subverts the politically circulated myth of home as a fixed centre by evoking in exile a dual response of longing as well as aversion. The duality inherent in the family photograph on the first page of One Man’s Bible generates a dialogic tension which helps the protagonist re-negotiate his relationship with the lost home. And that accounts for my choosing it as key datum for a Bakhtinean discourse analysis in the light of theories of exile with Edward Said as the main critical source. I also draw on Roland Barthes’ “Reflections on Photography” to demonstrate how at the surface level home symbolises all that is best in life—love, affection, intimacy, warmth, unity, security and shelter etc. At the deeper level, however, multiple other voices emerge to subvert the dominant construct of a single, stable, homogeneous home which demands unmixed loyalty from even from those who go out. The ‘chronotope’ of the photograph stirs up a whole series of foreign invasions, civil wars, colonial exploitation and domestic tyranny, all of which in turn open up the hidden structures of patriarchal power and hegemony at home which have been rendering the gender, sexual or generational other silent and invisible. A dialogic reengagement with the past thus grants Gao’s subject a Saidian double vision with which to dismantle the grand narrative of home as a site of Confucian order and harmony, and re-frame it as a complex, heterogeneous construct, which is responsible for ambivalence in exile’s response to it.